Identification of lactobacilli isolated from food by genotypic methods and MALDI-TOF MS - Dušková, Marta; Šedo, Ondrej; Kšicová, Kateřina; Zdráhal, Zbyněk; Karpíšková, Renáta (International journal of food microbiology, 2012)
Lactobacilli are bacteria with important implications in food and feed fermentation. Detailed knowledge of the lactobacilli composition is of high relevance to food and health control, various industrial or biotechnological applications, etc., but accurate identification of the Lactobacillus species is not an easy task. In this study, three methods, i.e. polymerase chain reaction (PCR), amplified 16S rDNA restriction analysis with restrictase MseI (16S-ARDRA), and the matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) were evaluated for their capabilities to identify Lactobacillus species. After comparison of the three methods on a set of 19 type/reference Lactobacillus strains, 148 strains isolated from dairy and meat products were characterized by PCR and MALDI-TOF MS. The strains were differentiated into nine and ten lactobacilli species by PCR and MALDI-TOF MS, respectively, with nine of these species being congruent. The success rates of species level assignment were 77% for PCR and 93% for MALDI-TOF MS that proved superior in the species identification. However, to differentiate between closely related Lactobacillus species, MALDI-TOF MS needs to be used in combination with genotypic techniques to achieve a more reliable identification.
Keywords: Food Microbiology; ribozomální DNA; Genotype; DNA, Ribosomal; Lactobacillus; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; polymerázová řetězová reakce; Polymerase Chain Reaction; Dairy Products; RNA, Ribosomal, 16S; maso; genotyp; Meat; fermentace; potravinářská mikrobiologie; Bacteria; mléčné výrobky; Fermentation; spektrometrie hmotnostní - ionizace laserem za účasti matrice; RNA ribozomální 16S